2021
DOI: 10.3389/fneur.2021.664610
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm Disorders and Corresponding Functional Brain Abnormalities in Young Female Nurses: A Preliminary Study

Abstract: Objective: Shift work is associated with a decrease in melatonin level and perturbation of the circadian rhythm; however, it is unknown if these lead to functional brain changes. In this study, we investigated whether circadian rhythm disorders caused by shift work are related to changes in brain functional connectivity (FC) and regional homogeneity (ReHo) using whole-brain resting-state functional magnetic resonance imaging (fMRI).Methods: This prospective case-control study included nine female night shift n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In addition to inflammatory cytokines, circulating levels of the circadian hormones melatonin and cortisol are central outputs of sleep but also regulators of the sleep–wake cycle themselves. Lower levels of melatonin were associated with lower sleep quality in healthy female nurses working night shifts compared with age-matched female nurses working the day shifts [ 56 ]. Furthermore, Mazzoccoli et al [ 57 ] found that elderly patients with advanced stage of lung cancer exhibited decreased melatonin levels and melatonin/cortisol ratios in the serum compared to healthy, age-matched controls.…”
Section: Recent Advances In How Sleep and Circadian Disruption Can Be...mentioning
confidence: 99%
“…In addition to inflammatory cytokines, circulating levels of the circadian hormones melatonin and cortisol are central outputs of sleep but also regulators of the sleep–wake cycle themselves. Lower levels of melatonin were associated with lower sleep quality in healthy female nurses working night shifts compared with age-matched female nurses working the day shifts [ 56 ]. Furthermore, Mazzoccoli et al [ 57 ] found that elderly patients with advanced stage of lung cancer exhibited decreased melatonin levels and melatonin/cortisol ratios in the serum compared to healthy, age-matched controls.…”
Section: Recent Advances In How Sleep and Circadian Disruption Can Be...mentioning
confidence: 99%
“…To date, numerous studies on functional abnormalities in SWD have been detected via functional magnetic resonance imaging (fMRI) (9,10). One study on night shift nurses has shown higher ReHo in the bilateral occipital lobe and left parietal lobe and lower regional homogeneity (ReHo) in the bilateral cerebellar hemisphere in contrast with the day shift nurses (10).…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies on functional abnormalities in SWD have been detected via functional magnetic resonance imaging (fMRI) (9,10). One study on night shift nurses has shown higher ReHo in the bilateral occipital lobe and left parietal lobe and lower regional homogeneity (ReHo) in the bilateral cerebellar hemisphere in contrast with the day shift nurses (10). Another study on SWD has revealed disrupted functional connectivity between default mode network and sensorimotor network, left frontoparietal network, and salience network (9).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, areas of pain processing, including for example middle cingulate cortex (MCC), postcentral gyrus from Study 1 and precentral gyrus, supplementary motor area (SMA) from Study 2; and regions of sensory processing, including Heschl’s gyrus, precuneus from Study 1 and paracentral lobule from Study 2 were detected. These regions are thought to contribute to migraine attacks (for a review see Schwedt et al, 2015 ), and some of them also associated with circadian rhythm-related phenomena in previous fMRI studies, including precuneus ( Kyeong et al, 2017 ; Facer-Childs et al, 2019 ), postcentral gyrus ( Kyeong et al, 2017 ; Fafrowicz et al, 2019 ), precentral gyrus ( Kyeong et al, 2017 ), posterior cingulate cortex (PCC) ( Kyeong et al, 2017 ), and MCC ( Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%